Клініко-морфологічне зіставлення у діагностиці захворювань передміхурової залози - Григор’єва, Ю. В.; Гичка, С. Г. (Clinical Endocrinology and Endocrine Surgery, 2010)
It was examined comparison of clinical diagnostic methods (digital rectal examination, transrectal ultrasound examination, serum prostate specific antigen level) and morphological examination by data of transrectal needle biopsies.